Shallow Seafloor Gas emissions Near Heard and McDonald Islands on the Kerguelen Plateau, Southern Indian Ocean. Issue 3 (16th March 2020) - Spain, E. A.; Johnson, S. C.; Hutton, B.; Whittaker, J. M.; Lucieer, V.; Watson, S. J.; Fox, J. M.; Lupton, J.; Arculus, R.; Bradney, A.; Coffin, M. F.
Abstract: Bubble emission mechanisms from submerged large igneous provinces remains enigmatic. The Kerguelen Plateau, a large igneous province in the southern Indian Ocean, has a long sustained history of active volcanism and glacial/interglacial cycles of sedimentation, both of which may cause seafloor bubble production. We present the results of hydroacoustic flare observations around the underexplored volcanically active Heard Island and McDonald Islands on the Central Kerguelen Plateau. Flares were observed with a split‐beam echosounder and characterized using multifrequency decibel differencing. Deep‐tow camera footage, water properties, water column δ 3 He, subbottom profile, and sediment δ 13 C and δ 34 S data were analyzed to consider flare mechanisms. Excess δ 3 He near McDonald Islands seeps, indicating mantle‐derived input, suggests proximal hydrothermal activity; McDonald Islands flares may thus indicate CO2, methane, and other minor gas bubbles associated with shallow diffuse hydrothermal venting. The Heard Island seep environment, with subbottom acoustic blanking in thick sediment, muted 3 He signal, and δ 13 C and δ 34 S fractionation factors, suggest that Heard Island seeps may either be methane gas (possibly both shallow biogenic methane and deeper‐sourced thermogenic methane related to geothermal heat from onshore volcanism) or a combination of methane and CO2, such as seen in sediment‐hosted geothermal systems. These data provide the first evidence of submarine gas escape on the Central Kerguelen Plateau and expand our understanding of seafloor processes and carbon cycling in the data‐poor southern Indian Ocean. Extensive sedimentation of the Kerguelen Plateau and additional zones of submarine volcanic activity mean additional seeps or vents may lie outside the small survey area proximal to the islands. Plain Language Summary: Bubbles are constantly escaping the seafloor, either from thick sediments with gas‐producing bacteria or from volcanic gases escaping rocks deep beneath the seafloor. We use sonar to observe bubbles that appear as "hydroacoustic flares" as they travel from the seafloor into the ocean. Our paper shows the results of the 2016 RV Investigator voyage to Heard and McDonald Islands, two of Australia's most remote islands and home to its only active volcanoes. We observed hundreds of flares around the two islands and were able to examine bubbles in some of our camera footage. By examining the seafloor, the shallow subseafloor, and the chemistry of sediments and the water column, we suggest the bubbles may be composed of different gases. Around Heard Island, bubbles were associated with thick sediment that are likely rich with bacteria that produce methane gas; near the McDonald Islands, bubbles were not associated with sediments and possibly indicate shallow volcanic activity emitting gases, like CO2, originating from the mantle. Knowing where bubbles are escaping is crucial for understanding how much gas is contributed from the seafloor into the ocean and atmosphere. Key Points: Active submarine gas emission around Heard and McDonald Islands on the Central Kerguelen Plateau in the southern Indian Ocean Gas release near the McDonald Islands possibly shallow diffuse hydrothermal venting, uncommon on an intraplate large igneous province Gas release near Heard Island either or both a biogenic orthermogenic methane seep, the second reported in the Southern Ocean to date